Government Dependencies in Logistics: A Case Study of Kazakhstan - Nurgeldina, Zhanna (2017)
The purpose of the dissertation is to investigate the nature of government dependency in logistics and inspire further research on interdependence between logistics and government. The research design is the case study of Kazakhstan. A case study is the most appropriate approach to investigate a real life situation. My experience as a practitioner observer gained in the central government agency of Kazakhstan has been applied as a methodological tool. There are a few empirical studies on government dependency in logistics, particularly in transitional economies such as Kazakhstan. The research findings might contribute to a better understanding of government dependency in supply chain management in transitional economies. Kazakhstan’s logistics industry has been developing under conditions of transitional economy. Besides, the country is characterised by substantial distances between regional centres and suppliers of raw materials and their end customers. Due to its unique geostrategic location, the country has a potential to offer an ever-expanding logistics opportunities to business world. This set of factors lies in its research focus on how government might influence logistics activities of businesses. The research results state that: first, in the case of transitional economy such as Kazakhstan, the government cannot act exceptionally as an enabler of efficient logistics or a source of friction in business involved in logistics; second, increasing role of nongovernment organisations in transitional economy such as Kazakhstan is important to strengthen the power of business involved in logistics.